Validity of Questions in The Application of STEM-EDP Learning Approach to Improve Students' Learning Outcomes on Ecological Materials at SMAN 11 Banda Aceh - Dara Tri Oktaviani Bulan; Muhibbuddin Muhibbuddin; Wiwit Artika; Cut Nurmaliah; Abdullah Abdullah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
The tool used in this study is a test device containing questions to measure the ability of students on ecological material. Questions that become an evaluation instrument need to be in accordance with the criteria for quality test questions such as those that must be valid. The method in knowing whether or not the questions used are valid must be tested for the validity of the questions. This study aims to identify the level of validity of the question items as an effort to increase student learning outcomes in ecological material. Sampling using purposive sampling technique with a sample of 30 people. The data collection technique was carried out by giving tests in the form of questions to students in the form of multiple choice, totaling 50 items and analyzed quantitatively using the help of SPSS Trial Version 24. The results of the analysis showed that each item had a different level of validity, with a percentage of validity. Of the 50 test items tested, 60% (n=30) questions were declared valid and 40% (n=20) items were declared invalid.Keywords: validity, question, learning outcomesAlat yang dipakai pada penelitian ini yakni perangkat tes berisikan soal dalam mengukur kemampuan peserta didik pada materi ekologi. Soal yang menjadi sebuah instrument evaluasi perlu sesuai akan kriteria soal tes yang bermutu antaranya yakni soal tersebut mesti valid. Metode dalam mengetahui valid ataupun tidak soal yang dipakai harus dilakukan uji validitas pada butir-butir soalnya. Penelitian ini tujuannya mengidentifikasi tingkat validitas item pertanyaan tes yang menjadi upayanya dalam menambah hasil belajar peserta didik dalam materi ekologi. Sampel diambil memakai metode purposive sampling dengan sampelnya berjumlah 30 orang. Teknik mengumpulkan data dilakukan dengan pemberian tes berupa soal kepada peserta didik dengan berbentuk pilihan ganda yang jumlahnya 50 item pertanyaan dan dianalis secara kuantitatif dengan menggunakan bantuan SPSS Trial Version 24. Hasil analisis menunjukkan bahwa masing-masing butir soal memiliki tingkat validitas berbeda, dengan persentase kevalidan dari 50 butir soal tes yang diujicobakan adalah 60% (n=30) soal disebut valid dan 40% (n=20) soal disebut tidak valid.Kata Kunci: validitas, soal, hasil belajar